2019
DOI: 10.3390/jcm8111984
|View full text |Cite
|
Sign up to set email alerts
|

Low Pre-Treatment Count of Circulating Endothelial Progenitors as a Prognostic Biomarker of the High Risk of Breast Cancer Recurrence

Abstract: Neoangiogenesis is mediated by circulating bone marrow-derived endothelial progenitors (circulating EPCs). The aim of the study was the quantification of circulating EPCs from the peripheral blood mononuclear cells of invasive breast cancer (IBrC) patients by flow cytometry, before and after cancer adjuvant treatment. A total of 88 stage IA-IIB primary IBrC patients were enrolled prospectively. Circulating EPCs with the immune-phenotype CD45−CD34+CD133+CD31+ were assessed. Treatment significantly reduced the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The number of circulating EPCs was determined using a method and recommendations provided by Mancuso et al and our previous study [ 15 , 16 ]. Pre-treatment blood samples collected with EDTA were analysed on the FACSCaliburTM (BD Bioscience, San Jose, CA, USA) for four-color immunophenotyping.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of circulating EPCs was determined using a method and recommendations provided by Mancuso et al and our previous study [ 15 , 16 ]. Pre-treatment blood samples collected with EDTA were analysed on the FACSCaliburTM (BD Bioscience, San Jose, CA, USA) for four-color immunophenotyping.…”
Section: Methodsmentioning
confidence: 99%
“…Circulating EPCs were thus defined according to the following immunophenotype: CD45−CD34+CD133+CD31+. The laboratory procedure is described in our former paper [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization definition, patients were classified into three BMI subgroups: normal weight (18.5 to 24.9 kg/m 2 ), overweight (25.0 to 29.9 kg/m 2 ), obese (>30.0 kg/m 2 ). Full details of the study recruitment and procedures were previously reported [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…These included the administration of adjuvant chemotherapy, immunotherapy, hormonal therapy, or a combination, as well as radiation therapy details including primary target (breast vs. breast and regional nodes, use of boost, and prescribed dose). None of the patients were taking any drugs with hemostatic and fibrinolytic effects [ 12 ].…”
Section: Methodsmentioning
confidence: 99%